Warming-up and evaporation characteristics of homogeneous and heterogeneous water droplets; International Journal of Heat and Mass Transfer; Vol. 138 - Antonov D. V. Dmitry Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Piskunov M. V. Maksim Vladimirovich; Vysokomornaya O. V. Olga Valeryevna; Yan Wei Mon (2019, 2019)
Title screen